Strategies for Overcoming Barriers to Improving Safety in Small Construction Organisations - Riza Yosia Sunindijo (Institute of Research and Community Outreach - Petra Christian University, 2015)
The majority of organisations in the construction industry are small organisations, how ever their safety performance is still far behind their larger counterparts. Therefore, it is important to focus on improving safety performance of small organisations so that the overall industry performance may be improved. Using a questionnaire survey, this research collected data from construction organisations based in New South Wales, Australia. Data analysis results have identified key barriers faced by small organisations when implementing safety. These barriers include the use of lowest bid price to evaluate tender submissions, lack of safety commitment from construction clients, and fierce competition. The analysis results have also revealed potential strategies for overcoming the barriers, such as including safety as an indicator in tender evaluation, more effective safety regulation enforcement by inspection and linking safety performance with insurance premium and licencing system, and subsidising safety training for small organisations. Improving safety performance in this sector cannot be done in isolation. The government, clients, and large organisations have important roles to play to change the norms and culture in the industry so that small organisations are supported in their effort to improve their safety performance.